Economic analysis of dairy production in Uganda, a case study on the performance of dairy cattle enterprises in Southwestern Uganda (Asian Journal of Agriculture, 2022)
Abstract. Waiswa D, Günlü A. 2022. Economic analysis of dairy production in Uganda, a case study on the performance of dairy cattle enterprises in Southwestern Uganda. Asian J Agric 6: 61-67. The economic performance of dairy cattle enterprises in Southwestern Uganda was analyzed in this study. A survey was conducted on 100 dairy cattle enterprises in Mbarara, Kiruhura, Lyantonde, Ibanda, and Isingiro Districts using data compilation forms covering the 2019/20 production year. The unit production cost of milk was determined as US$0.19L-1. Veterinary expenses had the largest share of the production costs at 24.94%, followed by labor costs, depreciation of the inventory value, other expenses, and feed costs, which contributed 14.11%, 12.46%, 11.96%, and 11.41%, respectively. Additional costs included the depreciation of animals, electricity and water, buildings, equipment and machinery, maintenance-repair, and general administrative expenses, which contributed 9.95%, 7.86%, 2.54%, 2.29%, and 2.48% to the total production costs, respectively. As a result, while the net profit of the enterprises was determined as US$1435.29, their financial profitability was 0.59, the profitability factor was 12.20, and the output-input ratio was 1.06. The overall profitability of the enterprises was affected mainly by the high veterinary expenses due to the high prevalence rates of tick-borne infections and the irrational distribution of capital elements. Therefore, measures to reduce the occurrence of tick-borne diseases are considered vital in lowering milk production costs, thereby increasing the profitability of enterprises.
Keywords: Dairy cattle enterprises, dairy production, economic analysis, economic performance